Analisis Gaya Bahasa Figuratif dalam Novel Dlum L Tajiffu Karya Byar Rufael (Kajian Stilistika) - Jamaung, Daeng Dullah; Akmaliyah, Akmaliyah; Mawardi, Mawardi (Riwayat: Educational Journal of History and Humanities, 2025)
his study aims to identify and analyze the figurative language styles used in the novel Dlum L Tajiffu by Byar Rufael through a stylistic approach. This study is conducted to reveal how the use of language styles strengthens the meaning, atmosphere, and message in literary texts. The method used in this research is descriptive qualitative with data collection techniques in the form of listening and note-taking methods on quotations containing figurative language styles. The data is analyzed using Qalyubi's stylistic theory which divides the language style into rhetorical and figurative categories. The results show that there are four dominant figurative language styles in the novel, namely metaphor, synecdoke, personification, and hyperbole, with metaphor as the most frequently used style. The use of these language styles provides an aesthetic effect and enriches the meaning of the narrative, as well as strengthens the characterization and atmosphere in the story. The findings show that figurative language plays an important role in building the novel's expressiveness and literary value.